Copper and zinc concentrations in atherosclerotic plaque and serum in relation to lipid metabolism in patients with carotid atherosclerosis - Tasić Nebojša M.; Tasić Danijela; Otašević Petar; Veselinović Mirjana; Jakovljević Vladimir; Đurić Dragan; Radak Đorđe (Vojnosanitetski Pregled)
Background/Aim. Some oligoelements are now investigated as possibly having a role in atherosclerosis. The aim of this study was to compare the concentrations of copper and zinc in the serum and carotid plaque and parameters of lipid metabolism in patients with different morphology of carotid atherosclerotic plaque. Methods. Carotid endarterectomy due to the significant atherosclerotic stenosis was performed in 91 patients (mean age 64 ± 7). The control group consisted of 27 patients (mean age 58 ± 9), without carotid atherosclerosis. Atheroscletoric plaques were divided into four morphological groups, according to ultrasonic and intraoperative characteristics. Copper and zinc concentrations in the plaque, carotid artery and serum were measured by atomic absorption spectrophotometry. Results. Serum copper concentrations were statistically significantly higher in the patients with hemorrhagic in comparison to those with calcified plaque (1.2 ± 0.9 μmol/L vs 0.7 ± 0.2 μmol/L, respectively; p = 0.021). Zinc concentrations were statistically significantly lower in plaques of the patients with fibrolipid in comparison to those with calcified plaques (22.1 ± 16.3 μg/g vs 38.4 ± 25.8 μg/g, respectively; p = 0.024). A negative significant correlation was found for zinc and triglycerides in the serum in all the patients (r = -0.52, p = 0.025). In the control group we also demonstrated a positive significant correlation for low-density lipoprotein cholesterol and copper in the serum (r = 0.54, p = 0.04). Conclusion. The data obtained in the current study are consistent with the hypothesis that high copper and lower zinc levels may contribute to atherosclerosis and its sequelae as factors in a multifactorial disease. Further studies are necessary in order to conclude whether high concentration of copper and zinc in the serum could be risk factors for atherosclesrosis.